The Role of Gender and Ethnicity in Perceptions of Rape and Its Aftereffects - Schneider, Lawrence J.; Mori, Lisa T.; Lambert, Paul L.; Wong, Anna O. (Sex Roles : A Journal of Research, 2009)
Caucasian-, Hispanic-, and Asian-American male and female students (n = 764) attending a California (USA) public university reported their perceptions of sexual assault. After reading a rape vignette, participants gave their impressions of the victim; estimated time needed for recovery and treatment; and recommended a sentence for the assailant. Half of the sample received information regarding state sentencing guidelines. Relative to female participants, males perceived the victim as more responsible. Caucasian-American males had stronger reservation about the victim’s judgment. Males were less inclined to assign blame than were females. Ethnicity was the only factor influencing perceptions of recovery. Ethnicity and sentencing guidelines, but not gender, impacted imprisonment decisions. Issues impeding a unified theoretical understanding of perceptions of rape victims were considered.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; californie; cours; discipline; intersectionnalité; perception; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; santé; sciences humaines; sex2283; thématiques; viol; violences; états-unis

Intersections: cultures, sexualités et genres - Brotman, Shari L.; Lévy, Joseph J. (Presses de l'Université du Québec, 2008)
Les intersections entre la culture, le genre et la sexualité retiennent aujourd’hui l’attention des chercheurs qui travaillent sur la diversité sexuelle, une tendance que l’on rencontre dans l’espace québécois et canadien. Plusieurs études ont ainsi porté sur ces enjeux parmi les autochtones et les groupes ethnoculturels. Cet ouvrage collectif, réalisé par des chercheurs, anglophones et francophones, de l’équipe pancanadienne Sexualités, Vulnérabilités et Résilience, présente ainsi un ensemble de travaux qui font le point sur ces questions. Les dimensions théoriques et méthodologiques sont ainsi cernées et des études empiriques, faisant appel à des approches quantitatives et qualitatives, traitent des trajectoires et des identités parmi différentes populations, des problèmes de santé auxquels elles peuvent être confrontées et des variations dans les usages sociosexuels d’Internet. Ce tour d’horizon aide à mieux comprendre la complexité des intersections touchant les identités sexuelles et les dimensions culturelles et suggère des pistes de recherche et d’intervention à développer.
Section: xvi, 474 pages ; 23 cm
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; identités LGBTQIA2+; intersectionnalité; premier cycle; psychologie; périodes historiques; queer; québec; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexologie; sexualité; thématiques; travail social

Sexual Attitudes and Double Standards: A Literature Review Focusing on Participant Gender and Ethnic Background - Fugère, Madeleine A.; Escoto, Carlos; Cousins, Alita J.; Riggs, Matt L.; Haerich, Paul (Sexuality & Culture : An Interdisciplinary Quarterly, 2008)
We conducted a review of literature regarding sexual attitudes and double standards, focusing on participant gender and ethnic background. We found that men had more permissive sexual attitudes than women, and that African Americans had the most permissive sexual attitudes, followed by White Americans, then by Hispanic Americans and Asian Americans. The literature regarding sexual double standards was mixed; some studies showed evidence of continued sexual double standards and some studies showed the absence of sexual double standards. In some studies, men were more likely to endorse the sexual double standard than women. We found only one article addressing sexual double standards using ethnic background as a quasi-independent variable; this research revealed that non-North American (Russian and Japanese) samples were more likely to endorse the traditional double standard, that sex is more acceptable for men than for women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; cours; discipline; europe; japon; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; russie; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques; états-unis

The Politics of Protection: Body Image, Social Pressures, and the Misrepresentation of Young Black Women - Poran, Maya A. (Sex Roles : A Journal of Research, 2006)
As part of a larger multi-method study, 15 Black women college students participated in focus group discussions on the body. Contrary to popular theories that propose that Black women are protected by a “Black Culture” that buffers them from negative effects of body representations—thereby leaving them with higher body esteem—the themes that emerged in the focus group discussions indicate that young Black women are indeed feeling (1) pressures to be thin, (2) pressures from the preferences of men of diverse ethnicities, (3) competition with other Black women in the realms of beauty, and (4) a strong sense of being misrepresented by media images of thin Black women. These results not only indicate that body image issues are of real pressing concern to young Black women, but that psychological research methodologies may be adding to the misrepresentation of young Black women and their struggles. Qualitative methods must be utilized in order to hear more clearly the voices of Women of Color.
Keywords: 2000 à aujourd'hui; 2000-2009; afro-féminisme; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; image corporelle; intersectionnalité; new york; premier cycle; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques; états-unis

Grossesse hors mariage dans les familles haïtiennes - Raphaël, Frantz (Santé mentale au Québec, 2006)
Des grossesses précoces chez des jeunes adolescentes haïtiennes de Montréal entraînent des situations de crise qui touchent plusieurs familles, en plus d’interpeller et d’impliquer des intervenants de diverses disciplines. Le sujet, abordé dans un contexte transculturel, fait référence au biculturalisme haïtien, tant en Haïti qu’en terre étrangère. Dans cet article, l’auteur aborde plus particulièrement la situation des Haïtiens dans le contexte québécois. L’analyse de l’attitude des parents des deux groupes culturels, occidentalisé et créole, constitue une lumière médiatrice dans les relations d’aide ou d’intervention psychothérapeutique. Dans la communauté haïtienne, les problèmes d’identité culturelle d’une part, et, le manque d’affiliation à la famille, d’autre part, sont à la base des conflits entre parents et enfants. L’auteur conclut avec des propositions dans le but d’améliorer l’efficacité des interventions avec ces familles dans leur processus d’adaptation migratoire.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; conflit familial; cours; discipline; grossesse hors mariage; haïti; justice sociale; maternité; montréal; premier cycle; psychologie; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexualité; thématiques

Pornography, Women and Feminism: Between Pleasure and Politics - Ciclitira, Karen (Sexualities, 2004)
This article draws on a qualitative research study which set out to explore women’s experiences and views of pornography within the broader context of conflicting feminist positions on pornography. The research methodology posed an implicit criticism of the kind of ‘findings’ familiar from mainstream psychological research: semi-structured interviews were conducted with women from diverse backgrounds in the UK, and feminist theory and discourse analysis were used to inform interpretation of their accounts. Although the question of feminism was not explicitly raised by the interviewer, it emerged as a recurrent theme in interviews, with interviewees suggesting that the feminist anti-porn stance in particular has influenced their perspective on pornography. Their accounts show that women’s experiences are variegated, individual and complex, and that discourses of pornography and feminism may be negotiated in unpredictable ways.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; europe; féminisme pop; pornographie; premier cycle; psychologie; périodes historiques; recherche qualitative; ressource en ligne; royaume-uni; régions géographiques; sciences humaines; sex1911; sexualité; thématiques

A quest for authenticity: Contemporary butch gender - Levitt, Heidi M.; Hiestand, Katherine R. (Sex Roles : A Journal of Research, 2004)
Un modèle d'identité butch contemporaine a été construit à partir de l'analyse d'une série d'entretiens semi-structurés avec des femmes identifiées comme butch qui ont décrit leur genre en relation avec leurs propres expériences et croyances. Le processus analytique impliquait une approche théorique fondée (Glaser & Strauss, 1967). Les résultats de l'étude décrivent comment les femmes identifiées comme butch conceptualisent leur identité de genre et comment cela affecte leurs relations sociales au sein des communautés lesbiennes et hétérosexuelles. La catégorie centrale de ce modèle (c.-à-d. Une quête d'authenticité) définit l'identité butch comme impliquant un processus continu de négociation entre un sens essentiel du genre lesbien et des exigences de présentation du genre qui sont comprises en relation avec la signification et la signification des genres à travers les contextes sociaux. . (Enregistrement de la base de données PsycINFO (c) 2019 APA, tous droits réservés)
Keywords: 2000 à aujourd'hui; 2000-2009; butch/femme; discipline; identités LGBTQIA2+; psychologie; périodes historiques; ressource en ligne; sciences humaines

Do Racial Minorities Respond in the Same Way to Mainstream Beauty Standards? Social Comparison Processes in Asian, Black, and White Women - CHIN EVANS, PEGGY; McCONNELL, ALLEN R. (Self and Identity, 2003)
Some members of stigmatized groups, such as Asian women, may be more likely to experience negative self-evaluations after exposure to a mainstream beauty standard than members of other stigmatized groups, such as Black women. In this study, 54 Asian women, 52 Black women, and 64 White women, were exposed to mainstream standards of beauty and compared themselves to these idealized images. It was hypothesized that although Black women would find these comparisons irrelevant, Asian women would see these targets as relevant for their comparisons, reflecting their striving for mainstream beauty standards. The results indicated that Black women did not find mainstream standards as relevant to themselves, and reported positive self-evaluations generally and about their bodies in particular. Asian women, on the other hand, responded differently than Black women and were more likely to endorse mainstream beauty standards in a similar fashion to White women. As predicted, Asian women also experienced greater dissatisfaction with their bodies than did Black women.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; corps; cours; discipline; intersectionnalité; premier cycle; psychologie; périodes historiques; racisme; représentation; ressource en ligne; régions géographiques; santé; santé mentale; sciences humaines; sex2283; sexisme; systèmes d'oppressions; thématiques; états-unis

Life with the first baby: women's satisfaction with the division of roles - Cappuccini, G.; Cochrane, R. (Journal of Reproductive and Infant Psychology, 2000)
The ways parents divide their roles after their first child is born is a particularly complex arena. The success of negotiations within this close personal relationship may be central to the future of the new family. Women and their partners were surveyed in late pregnancy and 6 months after the birth. Their attitudes to role division remained largely non-traditional after the birth, even though most of them had incorporated some traditional elements into their behaviour. Emotional support received from their partners was important to women's satisfaction with role division, which had fallen only slightly after the birth. Eight of the women were interviewed in depth to explore why it might be that satisfaction with role division tended to remain high after the birth, despite the division usually not being what they had hoped for. Contributory factors may include changes in emphasis in the division of breadwinning and the maintenance of overall responsibility for traditional role areas despite sharing of tasks.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; angleterre; approches et analyses; cours; discipline; europe; hétérosexualité; inégalités; maternité; premier cycle; privilèges; psychologie; périodes historiques; régions géographiques; sciences humaines; sexualité; soc2264; sociologie; systèmes d'oppressions; thématiques